Analyzing the Influence of Digital Wallet: Usage Intention and Trust in Mobile Payments on the Continuance Intention of University Students in Medan to Support an Inclusive Economy: Analisis Pengaruh Intensi Penggunaan Digital Wallet dan Trust in Mobile Payment Terhadap Continuance Intention Mahasiswa Kota Medan Dalam Penggunaan Berkelanjutan Aplikasi Pembayaran Digital Dalam Mendukung Ekonomi Inklusif - Arya Agung Nugraha; Sri Rezeki (Sekolah Tinggi Ilmu Ekonomi Eka Prasetya, 2025)
This study discusses the challenges of continuing the use of digital wallets among Medan students, where the adoption gap arises due to differences in the perception of benefits and the level of trust in mobile payment services. The background of the problem includes barriers from trust in mobile payments such as uncertainty of data security, and suboptimal technical experience so that initial intent tends to decrease. The research method is quantitative with a survey approach using online questionnaires that are distributed to students from various faculties. The techniques applied include testing the validity and reliability of the instrument, testing classical assumptions, and being processed with PLS SEM to evaluate the influence of digital wallets and trust in mobile payments on sustainable intentions. The results of the analysis revealed that these two functional and psychological variables simultaneously contributed significantly to shaping students' intentions to continue using digital payment applications. The synergy between superior features and security guarantees, supported by recommendations between friends, creates a strong value proposition and maintains the habit of cashless transactions.